Potensi Pembangkit Listrik Berbasis Energi Air Mikrohindro Bendungan Di Banten - Rahima Mahabbah; Ryan Adam Hidayatullah; Muhammad Rizky; Khaila Mardina Fauziah Awalia; Didik Aribowo (Fakultas Teknik Universitas Cenderawasih, 2024)
Banten Province has a number of dams that have the potential to be developed as micro hydro-based renewable energy centers. Micro hydro is a technology that utilizes water flow to produce electricity on a small scale, ideal for areas with abundant water resources. The dam in Banten, which was originally built for irrigation, flood control and raw water supply, can be optimized to produce environmentally friendly electrical energy. This research uses literature study methods and secondary data analysis to evaluate the potential of dams in Banten as a micro hydro renewable energy center. The data used includes official reports, scientific publications, and data from government agencies. The analysis includes evaluation of flow capacity and water fall height, as well as the environmental impact of implementing micro hydro technology. The research results show that several dams in Banten have adequate flow capacity and water fall height to support micro hydro installations. The environmental impact of micro hydro installations can be minimized by implementing existing best practices. Micro hydro development in Banten dams can reduce dependence on fossil energy and support the national renewable energy mix target. This research recommends the development of supportive policies and the participation of local communities to realize this potential. In this way, the dam in Banten can be transformed into a renewable energy center that contributes significantly to energy security and environmental sustainability in Indonesia.